Fiber-bundle illumination: realizing high-degree time-multiplexed multifocal multiphoton microscopy with simplicity. Issue 1 (December 2018) - Yu, Jiun-Yann; Kim, Sunduck; Shim, Young; Holland, Daniel; Allodi, Marco; Yeh, Chao-Yuan; Blake, Geoffrey; Han, Young-Geun; Guo, Chin-Lin
Abstract High-degree time-multiplexed multifocal multiphoton microscopy was expected to provide a facile path to scanningless optical-sectioning and the fast imaging of dynamic three-dimensional biological systems. However, physical constraints on typical time multiplexing devices, arising from diffraction in the free-space propagation of light waves, lead to significant manufacturing difficulties and have prevented the experimental realization of high-degree time multiplexing. To resolve this issue, we have developed a novel method using optical fiber bundles of various lengths to confine the diffraction of propagating light waves and to create a time multiplexing effect. Through this method, we experimentally demonstrate the highest degree of time multiplexing ever achieved in multifocal multiphoton microscopy (~50 times larger than conventional approaches), and hence the potential of using simply-manufactured devices for scanningless optical sectioning of biological systems.